SYNDROM DAWIDA. JAMES BALDWIN NA ZACHODZIE I W ROSJI - Ojcewicz, Grzegorz (Acta Neophilologica, 2006)
The article focuses on the reception of literary works by James Arthur Baldwin (1924-1987) in the West and in Russia. This classic of American literature showed himself to contemporary readers not only as a gifted prose writer, playwright and feature writer, but also as a radical social activist committed to the fight against American racism. The book Giovanni ’s Room, ranking among the golden hundred of the world literature of the second half of the 20th century, is regarded as the first American novel featuring homosexual love and an important voice in the fight against homophobia. Baldwin proves that we are slaves to the culture the main character, David, is a victim of.